Ethics in the liquid consumer society - Gutiérrez-Gómez, Edgar (2023)
The objective of this research is to analyze the ethical behavior of man and the sudden transformations of the ethicity of individual or social man, in relation to the surrounding world within the theory of liquid society, founded by Zygmunt Bauman. According to this theory, interpersonal relationships in contemporary society revolve around the ephemerality of friendships and sudden changes in behaviors established by the solidity of their old environment. The analysis of ethics in liquid society concludes that, necessarily, the ephemeral and consumerism are imposed; the stable forms of social relations that sustained the solid society are set aside.